(untitled) (Journal of Applied Oral Science, 2016)
Young swimmers are particularly susceptible to the onset of oral diseases. Objective To evaluate the oral health status in young competitive and non-competitive swimmers, involving an assessment of salivary cariogenic bacteria and secretory IgA (S-IgA) concentration. Material and Methods Before training sessions (T1), 54 competitive and 69 non-competitive swimmers had the following parameters assessed: decayed, missing, and filled teeth (DMFT), Plaque Index (PlI), and Gingival Index (GI). At T1 and after training sessions (T2), stimulated saliva was collected and microbiological and immunological analyses were performed. Results Competitive swimmers trained 2.02±0.09 hours 5 times a week, while non-competitive swimmers trained 2.03±0.18 hours a week. A total of 14.7% of competitive swimmers suffered dental trauma related to sports. Only 11.76% of the competitive swimmers took a daily dose of fluoride, against 32.65% of non-competitive swimmers (p=0.029). Neither group followed an established diet or presented statistically significant differences in terms of nutritional supplement drink and chocolate intake. There were statistically significant differences in terms of oral hygiene. No significant difference in clinical indexes (DMFT, PlI, and GI) was present. S. mutans was harbored by 18.6% of competitive and the 32.2% of non-competitive swimmers. S. sobrinus was detected in 22.03% of competitive and 91.6% of non-competitive swimmers (p